2021
DOI: 10.1186/s12870-021-02972-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional characterization of LEA genes during seed development process in linseed flax (Linum usitatissimum L.)

Abstract: Background LEA proteins are widely distributed in the plant and animal kingdoms, as well as in micro-organisms. LEA genes make up a large family and function in plant protection against a variety of adverse conditions. Results Bioinformatics approaches were adopted to identify LEA genes in the flax genome. In total, we found 50 LEA genes in the genome. We also conducted analyses of the physicochemical parameters and subcellular location of the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…To examine the potential functions of RING finger genes during the seed development process in flax, a published flax RNA sequencing (RNA-seq) dataset (NCBI GEO accession: ) ( Li et al, 2021 ) was used to confirm the expression profiles of these genes. A total of 505 RING finger genes were expressed at four stages (days after pollination [DAP]5, DAP10, DAP20, and DAP30) during the seed development process in flax, determined based on the transcriptome data; the other 69 genes were not found and excluded from the analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the potential functions of RING finger genes during the seed development process in flax, a published flax RNA sequencing (RNA-seq) dataset (NCBI GEO accession: ) ( Li et al, 2021 ) was used to confirm the expression profiles of these genes. A total of 505 RING finger genes were expressed at four stages (days after pollination [DAP]5, DAP10, DAP20, and DAP30) during the seed development process in flax, determined based on the transcriptome data; the other 69 genes were not found and excluded from the analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The RNA-seq data (accession number and ) ( Li et al, 2021 ; Zhang & Deyholos, 2016 ) were downloaded from the NCBI GEO dataset ( Tables S5 and S6 ) and filtered to explore the expression patterns of RING finger genes in flax. These transcript data ( Li et al, 2021 ; Zhang & Deyholos, 2016 ) were obtained for seeds at four developmental stages (DAP5, DAP10, DAP20, and DAP30) and for the AR and BR of the shoot apex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has been suggested that comparative TTG2 quantity in antipodal cells to gametes regulates seed size, indicating the role of the maternal and paternal dose-dependent molecular framework. The late embryogenesis abundant (LEA) protein family named LuLEA is expressed at later stages of seed development [ 26 ]. LuLEA1 negatively regulates seed size and yield as its higher expression reduces seed size and fatty acid content in Arabidopsis.…”
Section: Genetic Factors Controlling Seed Sizementioning
confidence: 99%
“…Different groups of LEA proteins show a low similarity [43]. Motif analysis in A. thaliana [36], ax (Linum usitatissimum) [44] and wheat [45] indicated that the members of LEA gene subfamily contain speci cally conserved structures. In our study, the conserved motifs of PnoLEA proteins were different among subfamily groups (Fig.…”
Section: Molecular Characteristics Of Pnolea Genesmentioning
confidence: 99%